Anatomic variation of the relation between the inferior mesenteric artery and the bifurcation point of abdominal aorta during lower anterior resection: A rare case report. - Zarokosta, Maria; Piperos, Theodoros; Chrysikos, Dimosthenis; Nikou, Eythumios; Flessas, Ioannis; Skarpas, George; Papapanagiotou, Ioannis; Tsiaoussis, Ioannis; Noussios, George; Mariolis-Sapsakos, Theodoros (Int J Surg Case Rep, 2018)
INTRODUCTION: Identification and ligation of the inferior mesenteric artery (IMA) is a crucial surgical step when performing lower anterior resection (LAR) for rectal cancer. Anatomic variations of the relation between the IMA and the bifurcation point of abdominal aorta (AA) encumber surgical maneuvers and are of great clinical importance. PRESENTATION OF CASE: An unusual anatomic variation of the relation between IMA and the bifurcation point of AA was unexpectedly detected during LAR to a 69-year-old Caucasian female patient. The operation was uneventful. A meticulous review of the recent literature was conducted as well. DISCUSSION: Variations of the mesenteric vascular supply are mainly identified incidentally, during the operation. In particular, variations of IMA are extremely uncommon in the literature. However, such kind of congenital variations, are not as rare as considered and their presence encumbers surgical maneuvers and increases the potentiality of intraoperative injury and hemorrhage. CONCLUSION: Surgeons' deep knowledge and unceasing awareness concerning probable anatomic variations of the relation between the IMA and AA, combined with detailed exposure of the operative field and of the relationship between these adjacent arteries constitute the cornerstone of a safe operation.